The Importance of Skills Development for Youth in the Current Context of Bangladesh: A Comparative Study and Path Forward - Assadekjaman, MD; Afroz, Nasreen (GILE Journal of Skills Development, 2025)
Bangladesh is positioned to harness the demographic dividend by leveraging the potential of its substantial influx of young workers joining the labour market annually. In the context of the fourth industrial revolution (4IR), modern labour markets globally have become increasingly competitive. This is particularly true in numerous least developed countries (LDCs), including Bangladesh. The quality of Bangladesh's workforce is facing diminished acceptance in both domestic and global labour markets. The jobless rate for graduates is threefold more than that of non-graduates, highlighting a contradiction in which education seemingly complicates work opportunities. This paper explores the causes of unemployment in contemporary Bangladesh and emphasizes the necessity for skills development to mitigate this issue. Annually, almost 2.2 million individuals, predominantly youth, enter the labour market in Bangladesh. This demographic advantage may be squandered if the expanding skills gap is not rectified, particularly given the disruptive influences of the Fourth Industrial Revolution (4IR), which necessitates a workforce equipped with both advanced technical and soft skills to maintain competitiveness in the global market. The study also reveals that a substantial proportion of these youths have undergone traditional schooling and obtained numerous certificates, although they lack the requisite technical skills, leading to a disparity between the competencies of graduates and the expectations of employers. As a result, young individuals face challenges in obtaining their preferred employment, resulting in a decline in national output. The report also proposes some areas that must be emphasized to promote skills development for young people in Bangladesh.